E-Government : Information, Technology, and Transformation. - Schnoll, Hans J. (Taylor and Francis, 2015)
This book presents a citizen-centric perspective of the dual components of e-government and e-governance. E-government> refers to the practice of online public reporting by government to citizens, and to service delivery via the Internet. E-governance represents the initiatives for citizens to participate and provide their opinion on government websites. This volume in the Public Solutions Handbook Series focuses on various e-government initiatives from the United States and abroad, and will help guide public service practitioners in their transformation to e-government. The book provides impor.